Sacred History for a Central Asian TownSaints, Shrines, and Legends of Origin inHistories of Sayrām, 18th-19th Centuries - Devin DeWeese (Revue des Mondes Musulmans et de la Méditerranée)
This article examines historical myths focused on Sayrām, a small town in the south of present-day Kazakstan, as a case study of indigenous conceptions of communal identity in pre-Soviet Central Asia. These traditions are preserved in a set of Turkic works, generically entitled « The History of Sayrām », which combine a « sacred history » of the town with a « sacred geography » in the form of a catalogue of local shrines ; the two components thus situate Sayrām both temporally and spatially within an Islamically-defined sacred universe, offering a vision of the town's participation in a historical framework hinging on the Prophet Muhammad's sanctifying homage to Sayrām, and an affirmation of the continuing presence and protection, through their shrines, of a host of Muslim saints (including both purely local figures and well-known personages of Islamic lore). These works, probably compiled in the 18th century and circulated most widely in the latter half of the 19th century, often reflect quite old narrative traditions evocative of Sayrām's role in the early Islamization of Central Asia ; they also reflect, however, the centrality of religiously-defined local and regional identities among the sedentary population of Central Asia prior to the changes brought on by the Russian conquest, the establishment of Soviet power, and the formulation of the new « national » identities that persist today.